Pemikiran KH. Hasyim Asy’ari tentang Persatuan - Muchamad Coirun Nizar (Endogami: Jurnal Ilmiah Kajian Antropologi, 2017)
KH. Hasyim Asy'ari is a national Islamic figure who existed in the early 20th century and contributed greatly to the Indonesian nation. His real contribution to the progress of Indonesian Muslims is the birth of the Nahdlatul Ulama organization which still exists and has many followers. This paper will describe  KH. Hasyim Asyari’s thought about unity in the book Al Muqaddimah Al-Qanun Al Asasi Li Jam'iyyah Nahdlatul Ulama 'as well as the historical socio-conditions that lie behind this thought. The idea of unity is the central idea in the book, and it included national unity and religious unity. His thought in this book is motivated by the social conditions that occurred at that time. The condition of the Indonesian nation being colonized by the Dutch is the most dominant social condition. The other social conditions are the religious social conditions that occur such as the emptiness of the leadership of the traditionalist Islam and the phenomenon of renewal in Islam